2015
DOI: 10.1177/1756287215574457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with temsirolimus in the treatment of advanced renal cell carcinoma

Abstract: Abstract:Temsirolimus is an inhibitor of the mammalian target of rapamycin (mTOR) kinase, a protein that has been shown to be particularly active in metastatic renal cell carcinoma (mRCC) with poor prognosis. Therefore, temsirolimus should be considered as the first-line treatment indicated in mRCC patients classified as poor risk. The benefits of temsirolimus are not limited to an increased survival but are also related to a better quality of life, which is certainly one of the most important aspects in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Approximately 25–30% of ccRCC patients present with metastatic disease at the time of diagnosis 5 . Recent advancements in ccRCC treatment strategies, including targeted therapies, have been achieved great therapeutic improvements 6 , 7 ; however, most treated patients eventually develop progressive disease due to acquired resistance 8 , 9 , resulting in poor prognosis. Insight into the mechanisms of ccRCC pathogenesis and progression may contribute to the development of novel strategies for the treatment of ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 25–30% of ccRCC patients present with metastatic disease at the time of diagnosis 5 . Recent advancements in ccRCC treatment strategies, including targeted therapies, have been achieved great therapeutic improvements 6 , 7 ; however, most treated patients eventually develop progressive disease due to acquired resistance 8 , 9 , resulting in poor prognosis. Insight into the mechanisms of ccRCC pathogenesis and progression may contribute to the development of novel strategies for the treatment of ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in case of sunitinib failure in advanced RCC, everolimus and axitinib appear to provide second-line PFS benefits [17]. On the other hand, recent Phase III Investigating Torisel as Second-Line Therapy (INTORSECT) trial reported no significant benefit of either temsirolimus or sorafenib as second-line treatment after sunitinib failure [7], though, temsirolimus demonstrated clinical efficacy as first-line therapy in poor risk patients [18]. Although sorafenib is a comparator agent in several clinical trials and often used as a second-line therapy, Chinese patients have been more responsive to sorafenib than western patients, hence, both sunitinib and sorafenib are widely recommended first-line therapies in China [19].…”
Section: Introductionmentioning
confidence: 99%
“…(1) mTOR Inhibitors Rapamycin and its analogues (rapalogs, e.g., sirolimus, temsirolimus, everolimus), which inhibit mTORC1 activity, are considered the first clinical PI3K signaling inhibitors [88]. Although temsirolimus is FDA approved for treating advanced renal cell carcinoma and everolimus is approved for the treatment of advanced breast cancer, nonfunctional gastrointestinal and lung neuroendocrine tumors, and renal cell carcinoma, rapalogs are not yet approved for the treatment of EC and are under development [89][90][91].…”
Section: Pi3k/akt/mtor Signaling Pathway Inhibitorsmentioning
confidence: 99%